Dementia in Aboriginal people in Residential Aged Care Facilities in Alice Springs: A Descriptive Study. Issue 2 (September 2019) - Hocking, Bruce; Lowe, Michael; Nagel, Tricia; Phillips, Caroline; Lindeman, Melissa; Farthing, Annie; Jensen, Heather; Cass, Alan; Dingwall, Kylie
Abstract: Background: A high prevalence of dementia among Aboriginal and Torres Strait Islanders has been reported but knowledge of underlying causes and associations remains limited. Objective: To identify the prevalence of factors that may be associated with the categories of Major neurocognitive disorders (Major NCDs) in Aboriginal people living in residential aged care facilities in Alice Springs in the Northern Territory (NT). Design and Setting: This descriptive cross-sectional study analysed clinical file and cognitive assessment data of participants who were identified as having cognitive impairment between January and June 2016. Method: Screening for the presence of cognitive impairment using the Kimberley Indigenous Cognitive Assessment (KICA) was undertaken and 58 of 84 Aboriginal people were admitted to the study. Using a clinical file audit, diagnoses of Major NCDs consistent with the DSM-5 classification were made and the prevalence of factors possibly associated with these diagnoses described. Results: Fifty of the 58 participants were diagnosed with a Major NCD. The most frequent diagnoses were Major NCD due to vascular disease (30%), Major NCD due to Alzheimer's Disease (26%) and Major NCD due to brain injury (20%). Hypertension, Type 2 Diabetes Mellitus and alcohol misuse were commonly reported together with hypothyroidism, hypoglycaemia and vitamin D deficiency. Conclusion(s): This study identified possible associations with Major NCDs in this population as well as a different spread of Major NCD diagnoses to previous studies in Aboriginal populations. There is a need for further research to understand the causes of dementia in Australian Aboriginal people and to use this information to appropriately tailor treatment and prevention programmes.